Комплексний аналіз сучасного технологічного стану виконання покрівельних робіт і розроблення пропозицій щодо їх удосконалення - Євтушенко, В. А. (Ways to Improve Construction Efficiency, 2014)
This article examines three main issues: the structure of waterproofing and roofing works, types of roofing materials, systematic and complex analysis of the current technical condition of the roofing production. Also, the article covers the implementation of new technological methods by using new roofing materials in practice of the construction.